The Reception of Al-Ṣūlī and Al-Āmidī of Metaphor in the Poetry of Abū Tammām through the Horizon of Expectations - bensefia, ridha; benyahia, abbas (El Omda in Linguistics and Discourse Analysis, 2022)
The research on Abu Tammam's metaphor aims to reveal its effect on the construction of the artistic image in his poetry. because it is full of artistic ambiguity, it compels the recipient to contemplate its poetry to reveal the relationship between the parts of the image. His poetry needs - for its pictorial richness - multiple readings. The metaphor is nothing other than an artistic means which deepens the astonishment of the receiver. It is not an artistic luxury that the poet uses to embed his text, hence the critics have launched a wide debate around this poetic